An Observational Study to Assess Brain MRI Change and Disease Progression in Multiple Sclerosis Clinical Practice—The MS‐MRIUS Study. Issue 3 (5th December 2016) - Zivadinov, Robert; Khan, Nasreen; Medin, Jennie; Christoffersen, Pia; Price, Jennifer; Korn, Jonathan R.; Bonzani, Ian; Dwyer, Michael G.; Bergsland, Niels; Carl, Ellen; Silva, Diego; Weinstock‐Guttman, Bianca
ABSTRACT: BACKGROUND & PURPOSE: To describe methodology, interim baseline, and longitudinal magnetic resonance imaging (MRI) acquisition parameter characteristics of the multiple sclerosis clinical outcome and MRI in the United States (MS‐MRIUS). MATERIAL & METHODS: The MS‐MRIUS is an ongoing longitudinal and retrospective study of MS patients on fingolimod. Clinical and brain MRI image scan data were collected from 600 patients across 33 MS centers in the United States. MRI brain outcomes included change in whole‐brain volume, lateral ventricle volume, T2‐ and T1‐lesion volumes, and new/enlarging T2 and gadolinium‐enhancing lesions. RESULTS: Interim baseline and longitudinal MRI acquisition parameters results are presented for 252 patients. Mean age was 44 years and 81% were female. Forty percent of scans had 3‐dimensional (3D) T1 sequence in the preindex period, increasing to 50% in the postindex period. Use of 2‐dimensional (2D) T1 sequence decreased over time from 85% in the preindex period to 65% in the postindex. About 95% of the scans with FLAIR and 2D T1‐WI were considered acceptable or good quality compared to 99–100% with 3D T1‐WI. There were notable changes in MRI hardware, software, and coil (39.5% in preindex to index and 50% in index to postindex). MRI sequence parameters (orientation, thickness, or protocol) differed for 36%, 29%, and 20% of index/postindex scans for FLAIR, 2D T1‐WI, and 3D T1‐WI, respectively. CONCLUSIONS: The MS‐MRIUS study linked the clinical and brain MRI outcomes into an integrated database to create a cohort of fingolimod patients in real‐world practice. Variability was observed in MRI acquisition protocols overtime.